CompTIA Network+ N10-006 : complete video course - Wallace, Kevin, 1965- (LiveLessons (Indianapolis, Ind.), 2015)
CompTIA Network+ N10-006 Complete Video Course is a comprehensive training course that brings CompTIA Network+ exam topics to life through the use of real-world demonstrations, animations, live instruction, and configurations, making learning these foundational networking topics easy and fun. Best-selling author, expert instructor, and double CCIE Kevin Wallace walks you through the full range of topics on the CompTIA Network+ N10-006 exam, including protocol reference models; network devices, topologies, and services; WAN technologies; network cables and connectors; network design; LAN technologies; network addressing and routing; unified communication; virtualization; network security; and network maintenance. This unique product contains multiple types of video presentations, including live instructor whiteboarding, real-world demonstrations, animations of network activity, dynamic KeyNote presentations, doodle videos, and hands-on router and switch CLI configuration and troubleshooting in real lab environments, enabling you to learn both the concepts and the hands-on application. The 200+ videos contained in this product provide you more than 17 hours of instruction. Modules are divided into easy to digest lessons and conclude with module review summaries. The product concludes with a series of lessons that give you valuable advice to help prepare for the actual exam. Designed to take you inside Network+ concepts in a unique and interactive way, CompTIA Network+ N10-006 Complete Video Course is guaranteed to help you master the foundational networking topics that will help you succeed on the exam and on the job.